2020
DOI: 10.1002/adbi.201900212
|View full text |Cite
|
Sign up to set email alerts
|

The Use of Genipin as an Effective, Biocompatible, Anti‐Inflammatory Cross‐Linking Method for Nerve Guidance Conduits

Abstract: A number of natural polymer biomaterial‐based nerve guidance conduits (NGCs) are developed to facilitate repair of peripheral nerve injuries. Cross‐linking ensures mechanical integrity and desired degradation properties of the NGCs; however, common methods such as formaldehyde are associated with cellular toxicity. Hence, there is an unmet clinical need for alternative nontoxic cross‐linking agents. In this study, collagen‐based NGCs with a collagen/chondroitin sulfate luminal filler are used to study the effe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
12
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 24 publications
(12 citation statements)
references
References 91 publications
0
12
0
Order By: Relevance
“…In this context, the crosslinking procedure applied to the nerve conduit can be critically relevant because it strongly affects its mechanical properties and stiffness and, consequently, the macrophage response [180]. Some of the chemical crosslinking agents commonly used are formaldehyde, hexamethylene diisocyanate, glutaraldehyde (GA), polyepoxy compounds, carbodiimides (EDAC, EDC) and genipin [180,188,189]. The effects induced by the crosslinking procedure on macrophages phenotype are described in a 2019 study by Kočí et al Here, they compared the effects of genipin and formaldehyde on collagen-based nerve guidance conduits.…”
Section: Chemical Modificationsmentioning
confidence: 99%
See 2 more Smart Citations
“…In this context, the crosslinking procedure applied to the nerve conduit can be critically relevant because it strongly affects its mechanical properties and stiffness and, consequently, the macrophage response [180]. Some of the chemical crosslinking agents commonly used are formaldehyde, hexamethylene diisocyanate, glutaraldehyde (GA), polyepoxy compounds, carbodiimides (EDAC, EDC) and genipin [180,188,189]. The effects induced by the crosslinking procedure on macrophages phenotype are described in a 2019 study by Kočí et al Here, they compared the effects of genipin and formaldehyde on collagen-based nerve guidance conduits.…”
Section: Chemical Modificationsmentioning
confidence: 99%
“…Conversely, these were more expressed in the conduits crosslinked with formaldehyde. Therefore, the results suggested that genipin crosslinking can be a valuable method to direct macrophages polarization towards an anti-inflammatory phenotype [188].…”
Section: Chemical Modificationsmentioning
confidence: 99%
See 1 more Smart Citation
“…Lyophilization of ECM-based biomaterials results in a porous microarchitecture. Our research group has successfully employed this approach to develop scaffolds for many indications including bone [35][36][37][38], cartilage [39][40][41], neural [42][43][44][45], respiratory [46], and cardiovascular [47][48][49][50] repair. Particular success has been achieved using lyophilized collagen scaffolds for osteochondral repair.…”
Section: Natural Polymer-based Approaches To Osteochondral Repairmentioning
confidence: 99%
“…21 Furthermore, GP has showed only a 0.01% of cytotoxicity than glutaraldehyde, and its in vivo biosafety has been extensively demonstrated. 15,22 The advantage of using GP instead of other chemical crosslinkers has been demonstrated in several applications, such as heart valves, 23 pericardial patches, 24 biomaterials for cartilage and nerves regeneration, 25 and decellularized tracheal transplantation. 26 Previously, we have developed biphasic collagen/hydroxyapatite scaffolds for cartilage and bone repair, respectively.…”
mentioning
confidence: 99%